Divan by Zîver :|a textual analysis and critical edition - Alten, Seçil. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
The subject of this thesis is the Dîvân, by Zîver, one of the Ottoman poets who lived in 18th century. The main aim of this study is to give information about Zîver’s life and literary personality and then to present and analyse the Dîvân in terms of form, content and language. For this purpose, I first compared the three manuscript copies of Dîvân and I prepared a critical edition of it. After a brief introduction, I examined Zîver’s life and literary personality, using information obtained from various sources. In the textual analysis part, I first evaluated Dîvân structurally. I determined verse forms and their distribution in the text, rhythm patterns, rhyme and repeated voices/words after rhyme. Then, I examined the language and expression styles of the text. Following this analysis, I examined the reflections of the religious and sufistic elements, social life and astrological elements in the poems. In addition, I studied the themes of lover and the beloved. In the final part, I put forward a description of the manuscripts that I had evaluated comparatively to define the relationship between them. Also, I mentioned orthographic characteristics and mistakes of the copyist of the YK copy. I then explained the methodology which I used in transcription and I demonstrated the schemas of transcription alphabets. A facsimile of the original manuscript is presented at the end of the study. (See Appendix A for an extended abstract.)